Engish grammar drills. - Lester, Mark, ....- (New York [etc.] : McGraw-Hill, 2009)
For learning grammar, you'll find the most success in retaining your skills through drills, drills, and more drills. English Grammar Drills reinforces your knowledge and enhances your ability to read, write, and speak in English. Each chapter deals with only one subject, so you are not overwhelmed with information and drills and can proceed at a comfortable pace. With close to 200 exercises you will get plenty of opportunities to practice what you have learned. Table of contents Introduction Nouns Pre-Noun Modifiers Post-Noun Modifiers Pronouns Noun Clauses The Six Basic Verb Forms The Three Tenses Perfect Tenses Progressive Tenses Modal Auxiliary Verbs Adverb Clauses Conjunction Questions Passive
Flaptitel: English grammar drills : gain confidence in your English grammar skills, review all essential grammar areas, practice with more than 150 exercises : perfect for beginning and intermediate learners!
Keywords: Engelse spraakkunst